2002
DOI: 10.1046/j.1469-8137.2002.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Below‐ground carbon input to soil is controlled by nutrient availability and fine root dynamics in loblolly pine

Abstract: Summary• Availability of growth limiting resources may alter root dynamics in forest ecosystems, possibly affecting the land-atmosphere exchange of carbon. This was evaluated for a commercially important southern timber species by installing a factorial experiment of fertilization and irrigation treatments in an 8-yr-old loblolly pine ( Pinus taeda ) plantation.• After 3 yr of growth, production and turnover of fine, coarse and mycorrhizal root length was observed using minirhizotrons, and compared with stem g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
181
4
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(211 citation statements)
references
References 53 publications
20
181
4
4
Order By: Relevance
“…This is in good agreement with Pregitzer et al (2002), who reported that the roots in an arbitrary fine-root size-class do not function the same way, and that their C cost for both construction and maintenance could be different (Pregitzer et al, 2002). King et al (2002) suggested that the term 'fine roots' is a mix of static and dynamic root fractions and that the size class below which root properties and function shift from those of perennial to ephemeral is much smaller than the commonly used 2.0 mm diameter class. ECM short roots include mostly first (tips are considered as first order) and second order short roots with primary structure, so that the results of King et al (2002) can be compared with those of Pregitzer et al (2002) and Guo et al (2004).…”
Section: Specific Root Length Within the Fine Root Systemsupporting
confidence: 87%
See 2 more Smart Citations
“…This is in good agreement with Pregitzer et al (2002), who reported that the roots in an arbitrary fine-root size-class do not function the same way, and that their C cost for both construction and maintenance could be different (Pregitzer et al, 2002). King et al (2002) suggested that the term 'fine roots' is a mix of static and dynamic root fractions and that the size class below which root properties and function shift from those of perennial to ephemeral is much smaller than the commonly used 2.0 mm diameter class. ECM short roots include mostly first (tips are considered as first order) and second order short roots with primary structure, so that the results of King et al (2002) can be compared with those of Pregitzer et al (2002) and Guo et al (2004).…”
Section: Specific Root Length Within the Fine Root Systemsupporting
confidence: 87%
“…King et al (2002) suggested that the term 'fine roots' is a mix of static and dynamic root fractions and that the size class below which root properties and function shift from those of perennial to ephemeral is much smaller than the commonly used 2.0 mm diameter class. ECM short roots include mostly first (tips are considered as first order) and second order short roots with primary structure, so that the results of King et al (2002) can be compared with those of Pregitzer et al (2002) and Guo et al (2004). Both studies showed that there is a decrease in SRL values with increasing root order and that SRL is smaller for roots with secondary structure.…”
Section: Specific Root Length Within the Fine Root Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other authors also found this strong dependence of root survivorship on root diameter (Gill and Jackson 2000;Wells and Eissenstat 2001;King 1,050, 1,540, 1,890 m a.s.l. 1,890, 2,380, 3, et al 2002;Baddeley and Watson 2005). This may be explained by higher nutrient concentrations and respiration rates of small diameter roots, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…There is clearly not a single class of "fine roots" that can be easily identified on the basis of morphological criteria (e.g., diameter, Pregitzer 2002) but, rather, a continuum of sizes, functions (Guo et al 2008), and lifespans (King et al 2002) across branching orders. Accordingly, the study of the elementary phases of root phenology (i.e., the onset of production and shedding of a root segment) would benefit from the consideration of multiple branching orders individually.…”
Section: The Phenology Of Fine Rootsmentioning
confidence: 99%